Honey improves lipid profile of diet-induced hypercholesterolemic rats - Nurmasitoh, Titis; Pramaningtyas, Miranti Dewi (Faculty of Medicine, Trisakti University, 2015)
BackgroundCoronary heart disease (CHD) is a major cause of morbidity and mortality throughout the world, including Indonesia. One of the risk factors for CHD is hypercholesterolemia. One of the natural products that has been developed for the treatment of hypercholesterolemia is honey. Honey contains fructooligosaccharides, various vitamins, minerals, and enzymes which are supposedly able to lower blood cholesterol levels. This research aimed to study the influence of honey on the levels of blood total cholesterol, triglyceride, and low density lipoprotein (LDL) levels in Wistar rats. MethodsThis study was of experimental post test control group design. Twenty-four male Wistar rats (Rattus norvegicus) were randomly divided into 4 groups. K1 was the negative control group (with normal diet), K2 was the positive control group (with high-fat diet), P1 was fed a high-fat diet for 7 days, followed by high-fat diet plus honey for the next 7 days. P2 was fed a high-fat diet for 7 days, followed by regular diet plus honey for the next 7 days. After completion of this treatment, total cholesterol, triglycerides, and LDL levels were measured by the cholesterol oxidase phenol+aminophenazone (CHOD-PAP) method using enzymatic spectrophotometry principles. ResultsThere were significant differences in total cholesterol, triglyceride, and LDL levels between all groups after day 15 (p<0.05). ConclusionHoney supplementation was able to reduce the blood levels of total cholesterol, triglycerides, and LDL. Honey supplementation accompanied by non-cholesterol feeds could more effectively lower total cholesterol, triglycerides, and LDL serum levels in Wistar rats.